Analisis Perbandingan Kemampuan Kewirausahaan Pengusaha Perempuan dan Laki-Laki: Studi pada UMKM di Kota Bandung - Sherlywati Sherlywati; Rini Handayani; Asni Harianti (Jurnal Manajemen Maranatha, 2017)
This study aim to compare the ability of women’s entrepreneurship and men’s entrepreneurship in the unit for Micro, Small and Medium Enterprises (SME) in Bandung City. Women’s entrepreneurship has a significant role in SME. Their great contributions support the economy of Indonesia. According Buchari (2013) women entrepreneur has the ability to predict the future (future oriented). They tend to view into the future when making a decision. In terms of predicting the state, women tend to be on the safe area (self player). While in terms of independence, male entrepreneurs tend to be more independent than women entrepreneurs. Several previous studies have said that there is a difference between entrepreneurial skills of women and men, but not significant. In this research, we want to see the difference entrepreneurial skills of women and men in SMEs in Bandung City. The sampling was done by cluster sampling method based on the administrative area of Bandung city and random sampling method. Respondents participated in demographic factors and factors of entrepreneurship abilities. Data analyzed by using SEM (Structural Equation Modeling) and processing with AMOS program. The results found in this study were 1). entrepreneurial men are more self-reliant in meeting the challenges of competition, 2). women entrepreneurs more willing to take risks and love the challenges above, 3). wirausaha more men to think for business development into the future to promote their business, 4). male entrepreneurs are more flexible and anticipation of environmental changes. Keywords: Men’s Entrepreneur; SMEs; Women’s entrepreneur